2018
DOI: 10.3389/fphar.2018.01388
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Achieving Opioid Analgesia Without Side Effects

Abstract: Opioids are the most effective drugs for the treatment of severe pain, but they also cause addiction and overdose deaths, which have led to a worldwide opioid crisis. Therefore, the development of safer opioids is urgently needed. In this article, we provide a critical overview of emerging opioid-based strategies aimed at effective pain relief and improved side effect profiles. These approaches comprise biased agonism, the targeting of (i) opioid receptors in peripheral inflamed tissue (by reducing agonist acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
164
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 190 publications
(252 reference statements)
3
164
0
1
Order By: Relevance
“…This is in agreement with our previous study, in which heat hypersensitivity was attenuated by perineurally applied exogenous opioids, but not by opioid peptides, including ENK, END, and DYN (53). Even though both exogenous and endogenous opioids activate the same opioid receptors, it is possible that these ligands initiate different downstream mechanisms to interact with various pain modality-dependent ion channels or intracellular pathways (36,53), and further studies are required. Interestingly, other studies found that M2 macrophages polarized by morphine or peroxisome proliferator-activated receptor-γ agonist reduced mechanical but not heat hypersensitivity in models of inflammatory and postoperative pain (28,54).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with our previous study, in which heat hypersensitivity was attenuated by perineurally applied exogenous opioids, but not by opioid peptides, including ENK, END, and DYN (53). Even though both exogenous and endogenous opioids activate the same opioid receptors, it is possible that these ligands initiate different downstream mechanisms to interact with various pain modality-dependent ion channels or intracellular pathways (36,53), and further studies are required. Interestingly, other studies found that M2 macrophages polarized by morphine or peroxisome proliferator-activated receptor-γ agonist reduced mechanical but not heat hypersensitivity in models of inflammatory and postoperative pain (28,54).…”
Section: Discussionsupporting
confidence: 92%
“…Together, our findings may have wide implications, since IL-4 and M2 cells play a role in inflammatory and neurodegenerative diseases (2,9,10,63). The opioid system may be particularly beneficial in peripheral neuroinflammatory conditions, since the activation of peripheral opioid receptors can provide analgesia without centrally mediated adverse effects (35,36). Nonetheless, our study does not preclude the search for strategies targeting other macrophage-derived mediators, including antiinflammatory cytokines and specialized proresolving mediators.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, activation of MOP receptors in the brain activates descending noradrenergic pathways, which leads to increased release of noradrenaline in the spinal cord (54,55). All above described effects underlay the opioid receptorinduced analgesia [reviewed by (26,41,(56)(57)(58)(59)(60)]. Additionally, the activation of NOP receptors in the brain can lead to hyperalgesia or anti-opioid actions in animal models (20,21,61).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal opioid receptors also mediate numerous side effects, such as respiratory depression, nausea, vomiting, reward/euphoria, dependence/withdrawal (MOP), convulsions (DOP), aversion/dysphoria, psychotomimesis (KOP), learning and memory impairment, motor disturbance, hypotension, bradycardia (NOP), sedation (MOP, KOP, NOP), constipation (MOP, NOP), and diuresis (KOP, NOP) [reviewed by (56,57,(64)(65)(66)(67)]. The main efforts are currently directed toward the development of novel ligands that exert analgesia with reduced side effects [reviewed by (57,68,69)].…”
Section: Introductionmentioning
confidence: 99%